1992
DOI: 10.1288/00005537-199208000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiation therapy for cervical lymph node metastases from an occult squamous cell carcinoma

Abstract: One hundred thirteen patients with cervical metastases from a squamous cell carcinoma and no evidence of the primary tumor were treated for cure by surgery and routine large-field postoperative irradiation. Patients were staged according to the 1987 American Joint Committee on Cancer (AJCC) classification. There were 24 N1, 54 N2, 29 N3, and 6 Nx lesions. One hundred four patients underwent cervical lymph node dissection and 9 had adenectomy. All patients received postoperative external beam therapy to the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 13 publications
2
32
1
3
Order By: Relevance
“…Strojan and Anicin [21] also reported a mucosal primary emergence rate of 9%, a neck relapse rate of 18%, a distant metastases rate of 11%, and a 5-year survival rate of 52% in a series of 56 patients treated with nodal resection and radiotherapy (given through extended portals in 48 patients). The data of six earlier reported series [22][23][24][25][26] combined are consistent with these findings. Of 389 patients, 370 received postoperative and 19 received preoperative radiotherapy, delivered to large-volume areas, including pharyngeal axis in virtually all patients.…”
Section: Comprehensive Irradiation Of Bilateral Cervical Nodes and Pusupporting
confidence: 85%
“…Strojan and Anicin [21] also reported a mucosal primary emergence rate of 9%, a neck relapse rate of 18%, a distant metastases rate of 11%, and a 5-year survival rate of 52% in a series of 56 patients treated with nodal resection and radiotherapy (given through extended portals in 48 patients). The data of six earlier reported series [22][23][24][25][26] combined are consistent with these findings. Of 389 patients, 370 received postoperative and 19 received preoperative radiotherapy, delivered to large-volume areas, including pharyngeal axis in virtually all patients.…”
Section: Comprehensive Irradiation Of Bilateral Cervical Nodes and Pusupporting
confidence: 85%
“…The stage of the neck disease dictates the overall prognosis for patients with carcinoma of the cervical lymph nodes in the absence of a known primary tumor site. Multiple retrospective studies have demonstrated better 5-year survival for N1 (65%-80%) versus N2 (40%-60%) and N3 disease (15%-30%) [16][17][18]. Traditionally, treatment of the N1 neck consists of a modified radical neck dissection followed by postoperative radiotherapy to the neck and to potential primary tumor sites (Waldeyer's ring).…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…In the literature, 5-year appearance rates of subsequent head and neck primary tumors vary from 2% to 54% (Table 3). Therefore, some authors advise an extended irradiation including prophylactic therapy of potential primary mucosal sites and both sides of the neck to minimize the risk of subsequent appearance of a primary tumor [2,6,15,24,30,35,38]. On the other hand, this treatment strategy is associated with side effects (especially chronic xerostomia) due to the increased irradiated volume [23].…”
Section: Extent Of Radiotherapy and Toxicitymentioning
confidence: 99%
“…Several prognostic factors in neck metastases from a CUP have been described: extracapsular extension [6,24,35], surgery/resection status [10,21,23,30], nodal status [5,6,12,15,23,24,33], histological grading [12,33], appearance of a subsequent primary tumor [5,12,23], nodal fixation [24], tumor localization [21], and pretherapeutic hemoglobin level [15].…”
Section: Prognostic Factorsmentioning
confidence: 99%